2007
DOI: 10.1002/bip.20910
|View full text |Cite
|
Sign up to set email alerts
|

Force spectroscopy of the fibrin(ogen)–fibrinogen interaction

Abstract: Fibrin aggregation is of vital importance in many physiological and pathological processes, such as blood coagulation, wound healing, and thrombosis. In the present study, we investigated the forces involved in the initial steps of the fibrinogen fibrin aggregation by force spectroscopy using the atomic force microscope. Our data confirm the existence of strong specific interactions between fibrin and fibrin(ogen), with unbinding forces ranging from 290 to 375 pN and a logarithmic dependence on the loading rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The protein-AFM tips functionalization process has been described elsewhere [8], [15], [16]. Briefly, cleaned AFM silicon nitride tips were silanized with 3-aminopropyl-triethoxysilane (APTES) for 1 h in argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The protein-AFM tips functionalization process has been described elsewhere [8], [15], [16]. Briefly, cleaned AFM silicon nitride tips were silanized with 3-aminopropyl-triethoxysilane (APTES) for 1 h in argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies by atomic force microscopy have shown that stretching and limited unfolding of fibrin monomers occur at lower forces (Brown et al 2007) than those required to detach a fibrin monomer from the lateral bonds holding it within the protofibril (Litvinov et al 2005;Brown et al 2007;Chtcheglova et al 2008).…”
Section: Relationship Between Filament Flexibility Bundling and Macrmentioning
confidence: 99%
“…The similarity of Young's moduli of fibrin protofibrils and fibres implies that the bonds holding protofibrils together within a fibre are strong enough to prevent protofibril slippage as a fibre is bent, and suggests that the compliance of the fibre comes from longitudinal stretching due to the flexibility of the superhelical coils formed by the three strands in the regions connecting the central and end domains. Recent studies by atomic force microscopy have shown that stretching and limited unfolding of fibrin monomers occur at lower forces (Brown et al 2007) than those required to detach a fibrin monomer from the lateral bonds holding it within the protofibril (Litvinov et al 2005;Brown et al 2007;Chtcheglova et al 2008).…”
Section: Relationship Between Filament Flexibility Bundling and Macroscopic Elastic Modulusmentioning
confidence: 99%
“…We have previously modeled aspects of fibrin polymerization [13,14], but in these models, we did not account for the fact that fibrinogen can bind with fibrin but not directly with other fibrinogen molecules. Oligomers of mixtures of fibrinogen and fibrin have been observed experimentally [12,[15][16][17], and these experiments suggest that this additional type of reaction affects the kinetics of the overall fibrin gelation process. With the ultimate goal of modeling the fibrin-fibrinogen system, here we look at a simplified model, in the belief that our study of it will usefully inform our analysis of the actual biological system.…”
Section: Introductionmentioning
confidence: 85%